Human keratinocyte-derived extracellular vesicles activate the MAPKinase pathway and promote cell migration and proliferation in vitro - Glady, Azela; Vandebroek, Arno; Yasui, Masato (Inflammation and Regeneration, 2021)
Wound healing is a complex biological process and complete skin regeneration is still a critical challenge. Extracellular vesicles (EVs) play essential roles in cell communication and cell regeneration, and recent studies have suggested that EVs may contribute to wound healing, though the molecular mechanisms behind this contribution remain unclear. For these reasons, we decided to use EVs isolated from human keratinocytes (HaCaT) in vitro to determine the potential mechanism of action of EV-derived wound healing. Scratch assays were used to determine cell migration and proliferation. Scratched cells were exposed to EVs in multiple conditions to determine how they affect wound healing. Statistical analysis between groups was carried out to using Student's two-sided t test. A p value of <  0.05 was considered statistically significant. We found that proteomic analysis of purified EVs shows enrichment of proteins associated with cell communication and signal transduction, such as MAPK pathways, and keratinocyte and fibroblast cultures exposed to EVs had higher levels of proliferation, migration, and ERK1/2 and P38 activation. Moreover, we found that treatment with specific ERK1/2 and P38 signaling inhibitors PD98059 and SB239063 impaired EV-mediated cell migration, which suggests that ERK1/2 and P38 signaling is essential for EV-induced wound healing. HaCaT cell-derived EVs accelerate the migration and proliferation of human keratinocytes and fibroblasts and may promote wound healing via the activation of MAPKinase pathways. These findings may be key in developing new methods to treat wounds and accelerate wound healing in the future.